THE ROLE OF BIG DATA IN DIGITALIZING INFORMATION - Elena COFAS (Scientific Papers Series : Management, Economic Engineering in Agriculture and Rural Development)
In a world increasingly shaped by data, its exponential growth demands global organizations to swiftly embrace and synchronize with the prompt evolution of our lives. Innovations in storage technology, the advent of IoT (Internet of Things), and the emerging regulations of the European Union, such as the General Data Protection Regulation (GDPR), all underscore how "Big Data" propels economic transformation. Amid the rapid proliferation of artificial intelligence and technology, Europe's digital overhaul assumes paramount importance, as recent crises underscore the urgency for more effective alternatives that fuel the imperative shift towards sustainability. The concept of "Big Data" has been integrated as a central pillar in the EU's digital transformation strategy, set for 2030, and consequently, within the ambit of its green strategy. This sector's inherent opportunities contribute to the EU's pursuit of climate neutrality by 2050. At its core, "Big Data" involves the amalgamation of extensive and diverse information, subjected to algorithmic analysis to drive decision-making. The data's significance extends beyond economic implications, permeating diverse domains such as safety, health, agriculture, environment, law, and even individual contexts, thereby accentuating the intrinsic essence of "Big Data”. This paper addresses the intricate demands posed by the rapid expansion of this type of data, which is experiencing exponential growth in terms of accessibility and automated integration within digital landscapes. Its efficacy is contingent upon not merely the escalating capabilities of technology to facilitate the accumulation and retention of substantial data quantities, but also on its proficiency to conduct thorough analysis, comprehension, and effective utilization of the data's complete worth.